L-band radiometry freeze/ thaw validation using air temperature and ground measurements. Issue 4 (3rd April 2018) - Williamson, Matthew; Rowlandson, Tracy L.; Berg, Aaron A.; Roy, Alexandre; Toose, Peter; Derksen, Chris; Arnold, Lauren; Tetlock, Erica
ABSTRACT: Assessment of remote sensing derived freeze/thaw products from L-band radiometry requires ground validation. There is growing interest in utilizing soil moisture networks to meet this validation requirement, although it remains unclear whether the current configuration of these networks is appropriate. To address this issue, a small-scale L-band radiometry study was conducted from November 2014 to April 2015 to capture F/T events. Soil moisture probes measuring soil temperature and real dielectric permittivity were installed within a surface-based L-band radiometer footprint vertically at the surface and horizontally at 2.5, 5 and 10 cm depths. A binary freeze/thaw product was derived using radiometer brightness temperatures and compared to the binary F/T classification using soil temperature, real dielectric permittivity and air temperature measurements. The results of the study found that shallow probe depths (vertical and 2.5 cm) resulted in an improvement in the radiometer F/T product accuracy over the standard 5 cm instrument depth currently utilized at soil moisture networks. Air temperature based approaches for validation result in lower accuracy for F/T events with no snow or wet snow, but performed similarly to soil measurements of temperature and permittivity during dry snow F/T events.